(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2022)
The contribution of Appropriate Conflict Resolution Methods to the Culture of Peace is of great value. In the present work, more attention is paid to Mediation, since its practice in the world acquires more and more recognition because it turns out to be adequate to build societies that live in a Culture of Peace. Their fields of action are multiple, in the sense that some are cases derived from the judicial system, organizations, educational institutions, family groups, among many others. The premise that has as a pillar of its work is: to look at conflicts as windows of opportunity to achieve positive and lasting changes in human relationships, thus overcoming the negative vision of it. Such positive changes generate and promote a culture of tolerance, of respect for diversity and peaceful coexistence among people and peoples, hence the importance of working and promoting an architecture of peace.